The Relationship Between Sitting Position and Length of Sitting with the Incidence of Low Back Pain in Tailors at Pasar 45 Manado - Tengor, Monica Magdalena; Anderson, Elisa (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Tailors are service providers to make clothes that work in a sitting position and long length of time due to working. Both sitting position and length of time are part of sewing activities and factors that can cause low back pain. The purpose of this study was to determine the relationship between sitting position and length of sitting with the incidence of low back pain in tailors at Pasar 45 Manado. This research method is cross-sectional, involving 45 respondents through a total sampling technique. The results of this study are most of the tailors, 24 (53.3%), have a moderate risk sitting position and 17 (37.8%) length of sitting at a moderate level with respondents experiencing mostly mild pain, and there is no significant correlation between sitting position and length of sitting on low back pain (p=0.609) and (p=0.095). Tailors are often exposed to pain, so tailors are looking for ways to anticipate or reduce pain, such as stretching or looking for a comfortable position, and because of covid-19, tailors have more free time to rest, relax, or do other activities that are not too burdensome for the tailor’s spine, also a decreased and uncertain workload and working time every day, which are the reason for no significant correlation. It is recommended for further researchers to examine other determinants such as workload and working period, as well as for tailors to perform ergonomic positions. Keywords : Low Back Pain, tailors, sitting position, ergonomic